Distribuição espacial e temporal das larvas de Chironomidae (Insecta: Diptera) na seção ritral do rio Cascatinha, Nova Friburgo, Rio de Janeiro, Brasil (Lundiana: International Journal of Biodiversity, 2004)
A study on the structure and distribution of Chironomidae fauna was carried out in a third order section of the Cascatinha River, Nova Friburgo, Rio de Janeiro, Brazil. The samples were taken out from four substrate types: litter from riffles, litter from pools, and sand and rock in erosional areas. A total of 4,973 larvae were collected, among which, those of Chironominae were the most abundant and diverse. The most abundant taxa were: Rheotanytarsus in the litter from riffles, Polypedilum in the litter from pools, Cryptochironomus in sand, and Cricotopus in rocks. The functional feeding groups predominant during the dry and rainy seasons were filtering-collectors and scrapers, respectively. In relation to substrate, the filtering-collectors were the most abundant in litter from riffles and rock, the gathering-collectors in litter from pools and the predators in sand. The shredders showed a low relative contribution in this study. The current flow, the nature of substrate and the food availability showed great influence on the distribution and structure of the chironomid community in the ecosystem.